2021
DOI: 10.18502/jri.v22i2.5802
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Balanced Chromosomal Translocation in an Azoospermic Male: A Case Report

Abstract: Background: Balanced translocation and azoospermia as two main reasons for recurrent pregnancy loss are known to be the leading causes of infertility across the world. Balanced translocations in azoospermic males are very rare and extensive studies need to be performed to elucidate the translocation status of the affected individuals. Case Presentaion: The cytogenetic characterization of a 28 year old male and his female partner is reported in this study. The male partner was diagnosed with non-obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Özcan et al [ 28 ] reported that a case of 22q11.2 deletion syndrome with azoospermia, and speculated that azoospermia can be one of the unknown clinical features of this syndrome. Chakraborty et al [ 10 ] reported a case of 46,XY,t(19;22)(19q13.4;22q11.2) with azoospermia. Gada Saxena et al [ 29 ] reported that a case of 46,XY,t(11;22)(q23;q11) showed male infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Özcan et al [ 28 ] reported that a case of 22q11.2 deletion syndrome with azoospermia, and speculated that azoospermia can be one of the unknown clinical features of this syndrome. Chakraborty et al [ 10 ] reported a case of 46,XY,t(19;22)(19q13.4;22q11.2) with azoospermia. Gada Saxena et al [ 29 ] reported that a case of 46,XY,t(11;22)(q23;q11) showed male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…[5] A large number of studies showed that balanced translocation may reduce fertility due to the production of unbalanced gametes. [7][8][9][10] Some studies showed that the breakpoint of chromosome translocation may disrupt or dysregulate important genes related to spermatogenesis, which lead to infertility. [7,11] The relationship between some breakpoints of chromosome and male infertility has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…De novo translocations are more perilous than inherited translocations. There may be multiple or triple reciprocal translocations at times [13].…”
Section: S Nomentioning
confidence: 99%
“…The most prevalent structural chromosomal abnormality observed in infertile males is significant deletions of the long arm of Y chromosome and robertsonian translocation. Y-chromosome microdeletion (YMD), occurring at a rate of 1% to 50%, is the second most common genetic cause of azoospermia which is closely linked to male infertility ( 2 , 5 ). Other than structural chromosomal aberrations and YMD, numerical sex chromosome anomalies like 47, XXY and the mosaic 45,X/46,XY karyotype are frequent sex chromosome defects in infertile males ( 6 ).…”
Section: Introductionmentioning
confidence: 99%